Duration of Electrocardiographic Monitoring of Emergency Department Patients With Syncope. Issue 11 (12th March 2019) - Thiruganasambandamoorthy, Venkatesh; Rowe, Brian H.; Sivilotti, Marco L.A.; McRae, Andrew D.; Arcot, Kirtana; Nemnom, Marie-Joe; Huang, Longlong; Mukarram, Muhammad; Krahn, Andrew D.; Wells, George A.; Taljaard, Monica
Abstract : Background: The optimal duration of cardiac rhythm monitoring after emergency department (ED) presentation for syncope is poorly described. We sought to describe the incidence and time to arrhythmia occurrence to inform decisions regarding duration of monitoring based on ED risk stratification. Methods: We conducted a prospective cohort study with enrolled adult patients (≥16 years old) presenting within 24 hours of syncope at 6 EDs. We collected baseline characteristics, time of syncope and ED arrival, and the Canadian Syncope Risk Score (CSRS) risk category. We followed subjects for 30 days, and our adjudicated primary outcome was serious arrhythmic conditions (arrhythmias, interventions for arrhythmias, and unexplained death). After excluding patients with an obvious serious condition on ED presentation and those with missing CSRS predictors, we used Kaplan-Meier analysis to describe the time to serious arrhythmic outcomes. Results: A total of 5581 patients (mean age, 53.4 years; 54.5% females; 11.6% hospitalized) were available for analysis, including 346 (6.2%) for whom the 30-day follow-up was incomplete and who were censored at the last follow-up time. A total of 417 patients (7.5%) experienced serious outcomes, 207 of which (3.7%; 95% CI, 3.3%–4.2%) were arrhythmic (161 arrhythmias, 30 cardiac device implantations, 16 unexplained deaths). Overall, 4123 (73.9%) were classified as CSRS low risk, 1062 (19.0%) medium risk, and 396 (7.1%) high risk. The CSRS accurately stratified subjects as low risk (0.4% risk for 30-day arrhythmic outcome), medium risk (8.7% risk), and high risk (25.3% risk). One-half of arrhythmic outcomes were identified within 2 hours of ED arrival in low-risk patients and within 6 hours in medium- and high-risk patients, and the residual risk after these cut points were 0.2% for low-risk, 5.0% for medium-risk, and 18.1% for high-risk patients. Overall, 91.7% of arrhythmic outcomes among medium- and high-risk patients, including all ventricular arrhythmias, were identified within 15 days. None of the low-risk patients experienced ventricular arrhythmia or unexplained death, whereas 0.9% of medium-risk patients and 6.3% of high-risk patients experienced them ( P <0.0001). Conclusions: Serious underlying arrhythmia was often identified within the first 2 hours of ED arrival for CSRS low-risk patients and within 6 hours for CSRS medium- and high-risk patients. Outpatient cardiac rhythm monitoring for 15 days for selected medium-risk patients and all high-risk patients discharged from the hospital should also be considered. Abstract : Supplemental Digital Content is available in the text.